The association between current smoking and binge drinking among adults: A systematic review and meta-analysis of cross-sectional studies - Molaeipour, Leila; Ghalandari, Maryam; Kangavari, Hajar Nazari; Alizadeh, Zeinab; Jafari, Elahe; Gholami, Fatemeh; Ghahremanzadeh, Neda; Safari, Shiva; Mohseni, Vahideh; Shahsavan, Masoumeh; Motevalian, Seyed Abbas (Frontiers in Psychiatry, 2023)
Background: The substantially increasing trend of binge drinking is a global alarm. Our aim was to undertake a systematic review and meta-analysis of cross-sectional studies to explore the association of current smoking with binge drinking among adults. Methods: We systematically searched Web of Knowledge; PubMed; Scopus; Embase and Ovid (from inception to 27 May 2020) databases to identify cross-sectional studies of the association between current smoking and binge drinking. Study screening, data extraction, and methodological quality assessment were all carried out by two independent authors. Adjusted Odds Ratio (AOR) was pooled with 95% confidence intervals (CI) using random effects model in the meta-analysis, followed by the investigation of the heterogeneity via Q-test and I2 statistic. We assessed publication bias using a funnel plot, the Egger's, and Begg's tests. Results: We identified 3171 articles and included ten cross-sectional studies with 66221 participants. A significant association was found between current smoking and binge drinking among both genders (AOR=2.97; 95% CI = 1.98 to 4.45; I2=90.5%). Subgroup analysis showed that this association among women, men, Caucasians, and Asians/Africans were (AOR= 3.68; 95% CI=1.03 to 13.18; I2=98.9%), (AOR=2.53; 95% CI=1.87 to 3.42; I2= 73.1%), (AOR=1.36; 95% CI: 1.01-1.83, I2=47.4%), and (AOR=3.93; 95% CI:2.99-5.17, I2=61.3%), respectively. There was no evidence of publication bias. Conclusions: Current smoking is associated with binge drinking and can be used for identifying and screening binge drinkers. Moreover, this association is stronger among men, and Asians/Africans.